Polemik dan Diskriminasi: Keterlibatan Anak dalam Penyalahgunaan Narkoba - Henky Fernando; Hasse Jubba; Yuniar Galuh Larasati; Syahrul Akmal Latif (Prodi Sosiologi FISIP Universitas Teuku Umar, 2022)
This study aims to describe the polemics and discrimination experienced by minors in their involvement in distributing and consuming drugs in Indonesia. This study uses a qualitative descriptive method with literature study data collection techniques by searching for relevant literature through online news pages on the internet using the search keyword